Inside Mt. Vesuvius: a new method to look at the seismic (velocity and attenuation) tomographic imaging - Edoardo Del Pezzo; Francesca Bianco (Annals of Geophysics, 2013)
New velocity and attenuation images of the geological structures below Mt. Vesuvius have been obtained using the programming facilities as well as the enhanced graphical power of Mathematica8TM. The velocity and attenuation space distributions, already calculated inverting respectively P-wave travel times and amplitude spectra of local VT quakes, are first optimally interpolated and then graphically represented in a new Mathematica8TM code notebook (a powerful computational document with more facilities than a simple code) developed by the present authors. The notebook aims at interactively and friendly representing 3D volume distributions of velocity and attenuation parameters. The user can easily obtain vertical sections (N-S, E-W, NE-SW and NW-SE oriented) and define color scales to represent velocity or attenuation variations or prefer iso-surface plots to represent the pattern of peculiar geological structures. The use of dynamic graphical representation, allowing the sliding of any (horizontal and/or vertical) slice through the volume under study, gives an unusual and powerful vision of any small velocity or attenuation anomaly. The (open source) code, coupled with the friendly use of internal routines of Mathematica, allows to adapt the graphical representation to any user necessity. The method appears to be particularly adapt to represent attenuation images, where the space variations of the parameters are strong with respect to their average. The 3-D plots of the interpolated velocity and attenuation fields enhance the image of Mt. Vesuvius structure, evidencing low-velocity associated with high attenuation anomalies which appeared unfocused in the plots reported by Scarpa et al. [2002] and De Siena et al. [2009].